Nutritional Implications of Trade-Offs Between Fresh and Processed Potato Products in the United Kingdom (UK) - Dogbe, Wisdom; Revoredo-Giha, Cesar (Frontiers in Nutrition, 2021)
The UK ranks eleven among world potato producing countries with annual per capita production of about 102 kg. Since 2007, the price of potatoes has increased by 44 per cent and UK households have shown a decreasing trend on their purchases of potatoes. At the same time, retailers and manufacturers have been introducing processed potato products, which also has affected the demand for fresh potatoes. This has shifted demand from fresh potatoes to unprocessed potatoes suggesting that consumers substitute fresh potatoes for processed ones. However, the extent to which this affect individual weekly nutritional composition is unknown. The objective of this study is to estimate the nutritional trade-offs between fresh and processed potatoes consumed in the UK using home scan panel dataset for Great Britain in 2018. Price and expenditure elasticities were estimated using the linearized version of the Exact Affine Stone Index (EASI) Demand System. Using estimated elasticities, we analysed the implications of substituting fresh potatoes for processed potatoes on nutrient intake. The results, in terms of the degree of substitution between fresh potatoes and processed potato products, suggest that consumers consider new potatoes baby and baking potatoes as substitutes for mashed potatoes. Maris piper potatoes and new potatoes baby are substitutes for frozen potatoes whilst white old potatoes and other vegetables and salads are complements to frozen potatoes. Finally, price reductions in the processed potatoes will increase average weekly caloric intake as well as the intakes of saturated fat and sodium. The latter has implications for public health as they are the major causes of cardiovascular diseases and certain cancers.